1979
DOI: 10.1177/016001767900400206
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Monetary and Fiscal Policies on Regional Business Cycles

Abstract: A Keynesian reduced-form quarterly model of regional income determination is constructed and tested for the eight regions of the United States. The results support the view that national economic policy exerts a significant direct influence on a region's export earnings. The findings are in conflict with some monetarist models, in that fiscal policy, as well as monetary policy, strongly influences regional basic economic activity. Also, the findings suggest the desirability of incorporating national policy var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…Moreover, these spillovers tend to be geographically dispersed. Carlino and DeFina () indicated a shortcoming of existing literature examining the regional effects of monetary policy (Beare, ; Garrison and Chang, ; Mathur and Stein, , etc.) in their attempt to measure monetary policy impacts region by region with no consideration of spillover effects among regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, these spillovers tend to be geographically dispersed. Carlino and DeFina () indicated a shortcoming of existing literature examining the regional effects of monetary policy (Beare, ; Garrison and Chang, ; Mathur and Stein, , etc.) in their attempt to measure monetary policy impacts region by region with no consideration of spillover effects among regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…She also finds that local disturbances contribute significantly to regional cycles and recommends that more research be done on the spillover effects from region to region. Garrison and Chang (1979) investigate the effects of fiscal and monetary policies and find that fiscal and monetary policies have quite different impacts on different regions. In particular, federal fiscal and monetary policies have large impacts on regions with a large concentration on the manufacture of durable goods and smaller impacts on agricultural and mining regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The synchronization between regions is not predominantly due to a large common exogenous force: evidence has shown that fiscal and monetary policies are not strong enough to enforce synchronization, and they operate on different regions with different strengths and different timing, see Garrison and Chang (1979), Kozlowski (1995), and Hooker (1996). In addition, we cannot explain the synchronization by referring to a common national business cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The market clearing conditions (5), (6), (10), the factor market conditions (7), (8), (9), (11), (12), factor mobility condition (4), and the government's budget constraint (13) determine the solutions to the variables l k Y l c Y K k Y K c Y wY w H Y rY r H , gY P. The above equations are algebraically manipulated to yield the following equation in r.…”
Section: Decisions Of Households and ®Rmsmentioning
confidence: 99%
“…The Garrison and Chang (1979), and Amos (1992). Mathur and Stein (1980) studied the regional impact of both federal ®scal and monetary policies.…”
Section: Introductionmentioning
confidence: 99%